2018
DOI: 10.1016/j.anaerobe.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

A 3D intestinal tissue model supports Clostridioides difficile germination, colonization, toxin production and epithelial damage

Abstract: Endospore-forming Clostridioides difficile is a causative agent of antibiotic-induced diarrhea, a major nosocomial infection. Studies of its interactions with mammalian tissues have been hampered by the fact that C. difficile requires anaerobic conditions to survive after spore germination. We recently developed a bioengineered 3D human intestinal tissue model and found that low O conditions are produced in the lumen of these tissues. Here, we compared the ability of C. difficile spores to germinate, produce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…While both their 3D model and our models have epithelial and fibroblast cells, albeit with different scaffolds, a key difference is the ability to control the apical and basolateral side environments using the VDC, which may be important when performing sensitive molecular studies. Similar to Shaban et al (2018), we show bacterial replication up to 48 h, although we also track bacteria that adhere to the epithelial layer. Additionally, we have a nanofiber scaffold incorporated between the epithelial and fibroflast layers, which creates a porous architecture similar to the basement membrane underlying the gut epithelium, along with myofibroblast cells in the basal layer.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…While both their 3D model and our models have epithelial and fibroblast cells, albeit with different scaffolds, a key difference is the ability to control the apical and basolateral side environments using the VDC, which may be important when performing sensitive molecular studies. Similar to Shaban et al (2018), we show bacterial replication up to 48 h, although we also track bacteria that adhere to the epithelial layer. Additionally, we have a nanofiber scaffold incorporated between the epithelial and fibroflast layers, which creates a porous architecture similar to the basement membrane underlying the gut epithelium, along with myofibroblast cells in the basal layer.…”
Section: Discussionsupporting
confidence: 65%
“…Three-dimensional models are known to promote more in vivo -like cell proliferation, growth differentiation, and cell-to cell contact (Kook et al, 2017). A recent study reported a 3D intestinal tissue model for C. difficile , where the authors demonstrated that C. difficile toxin activity was higher in comparison to a 2D transwell model (Shaban et al, 2018). They report that spores can germinate into vegetative cells within this model and that vegetative cells can survive up to 48 h, although the ability of C. difficile spores to germinate was similar in both their models.…”
Section: Discussionmentioning
confidence: 99%
“…Reproduced from [ 55 ], under the Creative Commons license; ( C ) Schematic of C. difficile infection in the 3D scaffold tissue model (left) and scanning electron microscopy of uninfected (left column) and infected with UK1 C. difficile 3D scaffolds (right column) at 4, 24 and 48 h (right). Adapted from [ 23 ].…”
Section: Advanced Tools For Modelling the Human Microbiome-gut-brain mentioning
confidence: 99%
“…Links between the gut microbiome and obesity, diabetes, liver disease, cancer, and neurodegenerative diseases [ 75 , 76 ] have now been established, which has driven considerable growth in this research area. Similar approaches to the co-culture models described herein have been utilised in this field, including monolayer/planktonic cultures [ 77 80 ] and 3D/planktonic cultures [ 81 , 82 ]. Reported methods to generate an in vitro environment that better represents the in vivo surroundings of the digestive tract include bioreactors [ 79 ], 3D organoid cultures [ 83 , 84 ], and organ-on-a-chip systems [ 85 ], all of which are described in detail by a review published in 2017 [ 78 ].…”
Section: Perspectives From Other Fieldsmentioning
confidence: 99%